Analyzing physical characteristics and shielding efficiency for non-lead medical radiation shielding sheets improved using PMMA. Issue 3 (3rd April 2019) - Kim, Seon Chil; Choi, Jeong Ryeol
ABSTRACT: Recently, the research for replacing heavy lead goods, such as medical radiation shielding sheets with environmentally friendly shielding materials has been widely carried out. The use of tungsten injected into the base material of polyethylene resin may be a good alternative for manufacturing lightweight shielding sheets. However, the increase of the mass ratio of tungsten in the shielding sheets is accompanied by the degradation of their physical properties such as tensile strength and flexibility. In this report, we have tried to fix this problem by adding Polymethyl Methacrylate (PMMA) to the mixing process of materials. If the portion of the added PMMA is 20%, it leads to a 25% increase of the particle packing ratio while there is a simultaneous 28% enhancement of tensile strength compared to before adding it. In the final test for shielding efficiency, it also turned out that the increase of the particle packing ratio for tungsten exhibits the same shielding efficiency as that of 0.2 mmPb. This consequence may imply that mass production of sheets that can prevent scattering rays in the medical radiation frequency range is possible through the calender process using a 0.3 mm tungsten sheet.